Complications and treatment of dens in dente: case report - Duque-Urióstegui, Cristhal; Palacios, Gabriela Castañeda; Duque-Urióstegui, Carla Brenda; López Portillo, Fernando Rosas; Ochoa, Veronica Vallejo; Peña, Nayeli Elizabeth Quintero; Cabrera Aguado, Diana Laura; Quintana, Erendira Delgado; Estrada, María del Rocío Flores; Estrada, Rosa Martha Flores; Medina, María de la Luz Sánchez; Mendoza, Víctor Manuel Arriaga; et al. (International Journal of Research in Medical Sciences, 2022)
Dens in dente is an anomaly of dental development characterized by focal or multifocal invaginations of the enamel in the dental papilla before its mineralization, it can result in additional layers of enamel, cementum, dentin or pulp tissue, it is also known as invaginated tooth or invaginated odontoma. The clinical case of an 18-year-old female patient is presented, she comes to the clinic for referring halitosis and purulent exudate for 1 month, a clinical and radiographic examination of tooth 22 was performed, a radiopaque invagination line was observed that penetrates the portion radicular in the cervical third, wide radiolucent area in the apical third, sinuous course and purulent exudate. Root canal treatment was performed with a flexible rotary system and canal obturation with a lateral technique and vertical compaction, restored with resin.